Implementation of open educational resources in the context of student-centred approach (Educational Dimension, 2025)
The article outlines pedagogical technologies for teaching environmental engineering in online learning systems of higher education using open educational resources (OER) with a student-centred approach. A technology integrating OER, including educational videos, online explanations for practical work, modular testing, and e-textbooks, was experimentally tested. The proposed technology was evaluated using a control and experimental group design at two universities. Statistical analysis using Pearson's chi-squared test showed a significant improvement in learning outcomes for the experimental group exposed to OER (χ2=45.55, p
Keywords: professional training; environment engineering; online learning environment; open educational resources